New geo-polymerization process for high strength alkali-activated binder with palm oil fuel ash and ground granulated blast furnace slag - Salih, Moslih Amer (2015)
This study investigated a new geopolymerization process for the production of high strength alkali activated binder, using high volume palm oil fuel ash (POFA) mixed with ground granulated blast furnace slag (GGBS). The experimental work was designed for the geopolymer paste and mortar. In the paste, the optimum alkali activation parameters of POFA were identified. These parameters included Sodium Hydroxide concentration, Solid/Liquid ratio (S/L), and Sodium Silicate to Sodium Hydroxide ratio (SS/SH). The role of curing regime and its effect on the alkali activation of POFA was investigated at ambient and different temperatures. GGBS was introduced as a partial replacement of POFA in five percentages (10-50%) to study the role of Calcium ions and mechanisms to improve the load bearing capacity of the resulting gel to a high strength geopolymer binder. The production of high strength geopolymerized mortar cured at ambient temperature was initially targeted by applying the activation parameters with the same replacement levels of GGBS as in the paste. The durability of the proposed alkali activated binder was investigated by exposing the mortar to extreme environments, namely elevated temperatures and sulfate attack. The compressive strength test, microstructural and chemical tests such as Scanning Electron Microscopy/Energy-Dispersive X-Ray Spectroscopy (SEM/EDX), X-Ray Diffraction (XRD), Thermogravimetric Analysis/Derivative Thermogravimetry (TGA/DTG), Differential Scanning Calorimetry (DSC) and Fourier Transform Infra-Red (FTIR), were conducted to study the underlying mechanisms of strength development. The results showed that liquid Sodium Hydroxide at 12 Molarity, S/L ratio at 1.32, and SS/SH ratio at 2.5 were applicable to alkali activate 100% POFA and produce geopolymer paste with 32.84 MPa at the age of 28 days. One major finding was identifying the Calcium Silicate Hydrate gel (C-S-H) as the main binding phase; with no Calcium Hydroxide Ca(OH)2 detected in the system. The test results showed that 100% POFA geopolymer paste can set and harden at ambient temperature with a comparable compressive strength to samples cured in the oven. Calcium ions dissolved from GGBS participated in increasing the binder strength by the formation of more C- S-H gel. Aluminum ions provided by GGBS led to a higher degree of polymerization and significant degree of crosslinking between C-S-H chains and shifting it to C-(A)-S-H gel. The compressive strength for binary geopolymer paste was 78.12 MPa at the age of 28 days. The alkali activated binder from the alkali activation of POFA as the only aluminosilicate material was able to produce geopolymer mortar with normal strength of 33.91 MPa at the age of 28 days. Inclusion of GGBS with POFA was effective to produce high strength geopolymer mortar with compressive strength of 70.25 MPa at the age of 28 days. Results from residual compressive test at elevated temperatures showed that samples maintained their dimensional stability at elevated temperatures due to the presence of evacuation routes (pore system) in the mortar which allowed water to be evaporated. Moreover, glass transition was detected between 600 ºC and 800 ºC which provided a relative increase in the strength of the geopolymer mortar. Test results showed that the proposed geopolymer mortar performed better than Portland cement mortar when exposed to sulfate attack. The results indicated that although Sodium sulfate and Magnesium sulfate had deterioration effect due to decomposing of Si and Ca ions from both C-S-H and C-A-S-H gels, the proposed geopolymer mortar experienced less strength depletion which can be related to the absence of calcium hydroxide in the matrix.